2021
DOI: 10.17083/ijsg.v8i4.448
|View full text |Cite
|
Sign up to set email alerts
|

A Serious Game to learn English: The case of Bethe1Challenge

Abstract: Current research in English language teaching reports that there is a tendency towards the use of mobile games and technology. However, there is a lack of research conducted that informs on the implementation of those strategies in high school contexts in Colombia. This article reports a case study aimed at exploring students’ perceptions towards the use of the Serious Game Bethe1Challenge supported with gamified activities, in a high school context during pandemic times. Accordingly, interviews, a pre-test an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 27 publications
1
3
0
Order By: Relevance
“…This occurs because the teachers thought the students like gamified things. This is accordingly with the previous studies on students' perception of the use of gamification in learning English that found the perceptions were positive (Abidin & Zaman, 2017;Aguilar-Cruz & Álvarez Guayara, 2021;Ariati & Iswahyuni, 2023;Putra & Priyatmojo, 2021;Zainiah et al, 2022). To make reading the students' routine, the teachers can also supply the students with exciting books.…”
Section: Discussionsupporting
confidence: 90%
“…This occurs because the teachers thought the students like gamified things. This is accordingly with the previous studies on students' perception of the use of gamification in learning English that found the perceptions were positive (Abidin & Zaman, 2017;Aguilar-Cruz & Álvarez Guayara, 2021;Ariati & Iswahyuni, 2023;Putra & Priyatmojo, 2021;Zainiah et al, 2022). To make reading the students' routine, the teachers can also supply the students with exciting books.…”
Section: Discussionsupporting
confidence: 90%
“…2 The Serious Game Be (the) 1: Challenge [21] relate that the SG Be (the) 1: Challenge is a game that was "specifically designed to strengthen English language learning processes" (p.68). This game was designed by the Ministry of Education in Colombia with the support of the British Council.…”
mentioning
confidence: 99%
“…This game can be played without internet connection, which is suitable for students in Colombia since internet connection is not stable in some areas of this country and there are some regions do not even have access to it. Additionally, [21] share that the SG Be (the) 1: Challenge has the following goals:…”
mentioning
confidence: 99%
“…"A Serious Game to learn English: The case of Bethe1Challenge", by Aguilar-Cruz and Álvarez Guayara [4], reports a case study aimed at exploring students' perceptions towards the use of the Bethe1Challenge serious game, supported with gamified classroom activities, which was used in a high school during pandemic times. To complement this study, interviews, a pre-test and post-test were implemented and analyzed.…”
mentioning
confidence: 99%